1984
DOI: 10.1093/ajcn/40.6.1175
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between glycemic response, digestibility, and factors influencing the dietary habits of diabetics

Abstract: A significant relationship was found between the rate of release of the sugars; glucose, maltose, and maltotriose from amylitic digestion of 10 foods tested in vitro (expressed as the digestibility index) and the blood glucose response to 50-g carbohydrate portions of the same foods eaten by diabetics (expressed as the glycemic index), (r = 0.815, n = 10, p greater than 0.01). The glycemic index related to both the palatability of the foods (r = 0.731, p less than 0.05) and their frequency of use (r = 0.698, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(34 citation statements)
references
References 30 publications
2
30
2
Order By: Relevance
“…In fact, based on the assumption that small intestinal digestion is a rate-limiting step, there is a hypothesis that traditional carbohydrate foods that are digested slowly in vitro are likely to give low glycaemic responses (O'Dea et al, 1981;Jenkins et al, 1984). We found no significant correlation between digestibility index and GI and II and therefore concluded that in vitro digestion would probably be Effects of African diets J-CN Mbanya et al of limited interest in the evaluation of these mixed meals.…”
Section: Discussionmentioning
confidence: 70%
“…In fact, based on the assumption that small intestinal digestion is a rate-limiting step, there is a hypothesis that traditional carbohydrate foods that are digested slowly in vitro are likely to give low glycaemic responses (O'Dea et al, 1981;Jenkins et al, 1984). We found no significant correlation between digestibility index and GI and II and therefore concluded that in vitro digestion would probably be Effects of African diets J-CN Mbanya et al of limited interest in the evaluation of these mixed meals.…”
Section: Discussionmentioning
confidence: 70%
“…The index allows ranking of carbohydrate foods on the basis of the rate of digestion and absorption (Jenkins et al, 1981;Englyst et al, 1992). In-vitro method has also been used to classify foods based on their digestion characteristics similar to the in vivo situation, and to identify slow release of carbohydrate in foods (Jenkins et al, 1984). The foods with GI values more than 70%, between 56% and 69% and lower than 55% were classified as high, medium, and low GI foods, respectively (Brand-Miller et al, 2003).…”
mentioning
confidence: 99%
“…Both Jenkins et al (1984) and Anderson et al (1984) did extensive research on the role of dietary fibre in the management of diabetes. Recent studies suggest that blood glucose may be influenced by various dietary fibres, although usually the most effective fibre sources for control of diabetes are soluble fibres such as guar gum and pectin (Slavin, 1991).…”
Section: Effects Of Soy On the Management Of Dia-betes Mellitusmentioning
confidence: 99%